Crianças em acolhimento institucional: brincadeiras, espaços e interações - OLIVEIRA, Luísa Sousa Monteiro (Universidade Federal do Pará, 2019)
The objective of this study was to investigate the play contexts in a host institution for children in Belém-PA as a microsystem by analyzing the activities, interactions and roles. The participants were 10 children from five to six years old, of both genders, with the host time ranging from one to 12 months. Two contexts were elected to be observe in participants in situations of play: the structured context (SC), represented by the toy library; and the semistructured context (SSC), represented by the shed, the playground and the pool. 117 records of five minutes were recorded, amounting to 585 minutes of observation. The results showed that regarding the activities, the symbolic play category was the most frequent (43.25%), followed by the physical contingency (35.04%) and the exploratory play (8.38%). The choice of play varied depending on the context, the symbolic obtained the highest number of occurrences in the SC and physical contingencies in SSC. The themes of the plays varied according to the gender variable; the girls played with themes related to family and home life; on the other hand, boys preferred to play with themes related to super heroes and the world of work. The choice of partners was also influenced by the context, although the highest percentage of partnerships occur with the coevals, the SSC, allowed the children to interact with a more diverse and larger group of partners, and allow the approach of sibling groups. Differentiated gender roles were perceived; the boys took over more roles of villains, superheroes, while girls preferred to take roles of mother, daughter, doctor, etc. It is considered that the host institution represented an elementary microsystem of development, which should ensure and encourage, among other skills, the engagement of children in a large and diverse array of plays. The study elucidates the need for flexibility in the use of spaces, promoting interaction between siblings, developing strategies for integration of the educators in the contexts and creating opportunities that encourage aproximate the family to interact in the plays with children.